The experiences of refugee Muslim women in the Aotearoa New Zealand healthcare system - Cassim S; Ali M; Kidd J; Keenan R; Begum F; Jamil D; Abdul Hamid N; Lawrenson R (Taylor and Francis Group, 2022)
This study explores the experiences of refugee Muslim women as they accessed and navigated the healthcare system in Aotearoa New Zealand (NZ). A case-oriented approach was used, where semi-structured interviews were carried out with nine Muslim women who arrived in NZ as refugees. Interviews were carried out in 2020, in Hamilton, NZ. Analysis involved a ‘text in context’ approach which employed an iterative and interpretive process, by engaging with participant accounts and field notes to unpack the various meanings behind the experiences of the participants in relation to the literature as well as the broader socio-cultural contexts in which these experiences occurred. The findings of this research identified various structural barriers to accessing healthcare such as cost and issues with interpreters, as well as instances of othering in the healthcare settings experienced by refugee Muslim women. In order to tackle inequity in the health system, structural and institutional barriers need to be addressed first, to prompt other levels of othering and discrimination to reduce over time.